Islamic Home Financing Research: A Bibliometric Mapping and Future Research Directions - Intan Dita Angelina; Wahyudi, Rofiul; Akhmad Arif Rifan; Sunu Prasetya Adi (Universitas Ahmad Dahlan, 2025)
The increasing demand for housing financing based on Islamic principles has positioned Islamic Home Financing (IHF) as one of the fastest-growing products within the Islamic banking industry. This phenomenon has triggered a range of academic studies exploring aspects such as financing contracts, consumer behaviour, affordability, and regulatory frameworks. However, these studies remain fragmented, lacking a comprehensive overview of the knowledge structure and research trajectory within the field. This study aims to map the scholarly landscape of IHF through a bibliometric analysis focusing on three main dimensions: co-authorship, co-occurrence, and co-citation. Based on 54 Scopus-indexed documents published between 2000 and 2025, the data were analyzed using VOSviewer. The findings indicate that collaboration networks are dominated by Hanudin Amin from Malaysian institutions, with emerging cross-country and cross-disciplinary partnerships that include sustainability issues. Keyword analysis highlights